2014
DOI: 10.1152/ajpcell.00084.2014
|View full text |Cite
|
Sign up to set email alerts
|

Type-2 pericytes participate in normal and tumoral angiogenesis

Abstract: Tissue growth and function depend on vascularization, and vascular insufficiency or excess exacerbates many human diseases. Identification of the biological processes involved in angiogenesis will dictate strategies to modulate reduced or excessive vessel formation. We examine the essential role of pericytes. Their heterogeneous morphology, distribution, origins, and physiology have been described. Using double-transgenic Nestin-GFP/NG2-DsRed mice, we identified two pericyte subsets. We found that Nestin-GFP(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 300 publications
(198 citation statements)
references
References 83 publications
7
185
0
6
Order By: Relevance
“…Promisingly, injection of adventitial cells sorted from the human saphenous vein improved blood flow recovery following mouse hind limb ischemia and led to the formation of a denser network of capillaries and arterioles as compared to vehicle controls, suggesting the presence of a proangiogenic environment (Campagnolo et al, 2010). In addition, type 2 (nestin+/NG2+), but not type 1 (nestin-/NG2+) pericytes facilitated partial recovery following hind limb ischemia, and were found to form part of the new vessel wall (Birbrair et al, 2014b). Furthermore, Matrigel implantation of human endothelial and pericyte co-culture results in neo-formation of the microvasculature, with perfusion and anastomoses with murine blood vessels (Dar et al, 2012).…”
Section: Vascularisationmentioning
confidence: 94%
See 2 more Smart Citations
“…Promisingly, injection of adventitial cells sorted from the human saphenous vein improved blood flow recovery following mouse hind limb ischemia and led to the formation of a denser network of capillaries and arterioles as compared to vehicle controls, suggesting the presence of a proangiogenic environment (Campagnolo et al, 2010). In addition, type 2 (nestin+/NG2+), but not type 1 (nestin-/NG2+) pericytes facilitated partial recovery following hind limb ischemia, and were found to form part of the new vessel wall (Birbrair et al, 2014b). Furthermore, Matrigel implantation of human endothelial and pericyte co-culture results in neo-formation of the microvasculature, with perfusion and anastomoses with murine blood vessels (Dar et al, 2012).…”
Section: Vascularisationmentioning
confidence: 94%
“…While both subpopulations are present in vessel vasculature, Birbrair et al showed that only Type 2 pericytes induce ECs to form new blood vessels in vivo and participate in tumour angiogenesis in vivo (Birbrair et al, 2014b). Ultimately, the damaged environment determines the distinction process as to whether multipotent pericytes become vascular smooth muscle cells, differentiate into progenitors or undergo both processes.…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Migrating endothelial cells proliferate in the surrounding extracellular matrix towards the angiogenic stimulus using integrins and other adhesion molecules. Periendothelial cells and pericytes are then recruited to promote vessel maturity (Birbrair et al 2014). …”
Section: Angiogenesismentioning
confidence: 99%
“…T he term 'angiogenesis' refers to formation and development of new blood vessels (neovascularization) from the pre-existing ones (Birbrair et al, 2014;. It is a multi-step and complex physiological process, essential for development (Yoo and Kwon, 2013), growth (Van Lessen et al, 2015) and wound healing ( Johnson and Traci, 2014).…”
Section: Introductionmentioning
confidence: 99%